Iron(III) complexing ability of new ligands based on natural γ-pyrone maltol. (1st September 2020) - Fusi, S.; Frosini, M.; Biagi, M.; Zór, K.; Rindzevicius, T.; Baratto, M.C.; De Vico, L.; Corsini, M.
Graphical abstract: Two new Fe(III) ligands based on natural γ-pyrone maltol were synthetized with the aim to obtain compounds with potential use as an oral therapy for iron deficiency. Highlights: New maltol derivatives were synthetized and characterized. Their iron(III) chelation ability was studied in aqueous solution. Antioxidant and antiradicalic properties of ligands were evaluated and compared to maltol itself. Abstract: Two new hydrophilic maltol derivatives were prepared with the aim of designing a chelator able to solubilize Fe(III) by complexation in physiologic condition. Sodium 2-((2-methyl-4-oxo-4H-pyran-3-yl)oxy)malonate (3 ) and lithium 2-((3-hydroxy-4-oxo-4H-pyran-2-yl)methyl)malonate (7 ) were prepared and characterized by 1 H- and 13 C NMR and their antioxidant properties were evaluated. The results indicate that the hydroxyl radical scavengers activity measured by deoxyribose degradation method, was comparable to maltol (Malt) itself (IC50 5.58 ± 0.76, 2.14 ± 0.46 and 2.44 ± 0.1 of (7 ), (3 ) and Malt respectively). However, the antiradical activity measured by DPPH method, follows the order (7 ) > (3 ) > Malt (IC50 3.15 ± 0.40; 4.96 ± 0.29; >7 mM, respectively). Additionally, their Fe(III) chelation ability was investigated in aqueous solution by means of electrochemical, various spectroscopic (UV–Vis, IR, EPR and Raman) and computational methods. The spectroscopic and theoretical elucidation indicates the main bidentate nature of ligand (3 ), coordinated via deprotonated carboxylic oxygen atoms of malonate moiety, while ligand (7 ) may coordinate also through phenolic and carbonyl oxygen atoms of maltol unity. Moreover, cyclic voltammetry studies suggest that the reduction of ferric complexes to more labile Fe(II) species proceeds in dissociation of the starting complexes. The obtained results point out the potential of these ligands in oral iron supplementation therapy.